Qurban Distribution System: A New Dimension Towards A Fair And Equitable Distribution - Md Salleh, Jismi; Mohd Omar, Mohd Hanif; Karim, Mohd Syazwan; Sulaiman, Shahitul Badariah; Kedin, Nor Adila; Mahat, Mohd Amran; Suyurno, S Salahudin; Ramlan, Aini Faezah (2020)
Qurban is a form of special Islamic ritual which is performed by slaughtering sacrificial animals and distributing the meat to the specified categories of recipients. In Malaysia, it is a common practice that mosques organised qurban on behalf of third parties and handled the entire process of qurban including its distribution. In the absence of a formal internal control system, the qurban distribution might be subject to mishandling. For instance, there is a risk that the distribution might not be made to the poor and needy at the appropriate rate, thus creating substantial doubt on whether the ritual performed has met the religious requirements or not. In order to mitigate the overall risks in qurban distribution, a group of researchers from UiTM Melaka has proposed a Qurban Distribution System (QurDiS). QurDiS is a documented internal control system consisting of policies, procedures and guidelines for qurban distribution in order to achieve a fair and equitable distribution. The system consists of various internal control activities including adequate segregation of duties among committee members, the use of specially labelled containers for meat distribution, policy of distribution over the counter only, maintenance of a computerised database of qurban recipients, acknowledgement of receipts of the distribution and reconciliation of the distribution through the preparation of distribution reports. The application of QurDiS has many advantages such as to promote transparency and accountability and to reduce the risk of unfair and forbidden distribution. QurDiS may be applied suitably by mosques and other managers of qurban.